Effects of a self-management support program delivered through telehealth services on self-management behaviors to delay renal impairment in public health volunteers with type 2 diabetes: 10.55131/jphd/2025/230313 - Rattanadachakul, Rakchanok; Rerkluenrit, Juntima; Rukchanok Koshakri (Journal of Public Health and Development, 2025)
Diabetes is a major global public health problem, and patients have a high risk of complications and mortality. Changing patient behavior through telehealth monitoring can help reduce the risk of chronic kidney complications. This experimental study aimed to evaluate the effectiveness of a self-management support program delivered through telehealth services in improving self-management behaviors to delay kidney deterioration in healthy volunteers with type 2 diabetes. The sample was selected through multistage random sampling and consisted of 102 participants, who were divided into experimental and control groups with 51 participants each. The experimental group participated in a self-management support program based on Lorig and Holman’s self-management concept, focusing on six key self-management skills. The program included health education delivered through videos, self-management behavior tracking, and communication through the LINE application. A questionnaire was used to assess self-management behaviors related to delaying kidney deterioration, particularly in terms of food consumption and exercise. The study duration was 12 weeks. Data were analyzed using descriptive statistics, independent t-tests, and paired t-tests. After the experiment, the experimental group had significantly higher mean scores for eating and exercise behaviors (M = 71.47, SD = 9.31) than those recorded before the program (M = 47.39, SD = 9.06) (p < .001). These findings suggest that a self-management support program delivered through telehealth can effectively promote behavior modification, particularly in maintaining normal blood sugar levels, which may help prevent kidney failure in individuals with type 2 diabetes. The study recommends further research to compare blood sugar levels (hemoglobin A1C) and their effect on glomerular filtration rates before and after the intervention. It also highlights the importance of closely monitoring the behaviors of health volunteers with type 2 diabetes from its onset.